Optimalisasi Pengolahan Limbah Peternakan Menjadi Pupuk Organik sebagai Upaya Peningkatan Pendapatan Pada Peternakan Kambing Perah Toni Farm Payakumbuh: Implementation of Livestock Waste Conversion into Organic Fertilizer to Improve Farmers' Income at Toni Farm, Payakumbuh - Roni Pazla; Yolani Utami; Sepri Reski; El Latifa Sri Suharto; Ferawati Ferawati; Tevina Edwin; Reswati Reswati; Arief Arief; Zaitul Ikhlas; Dyana Dahlya; Fatimah Aini; Gabrel Bati Suta (LPPM Universitas Andalas, 2026)
Toni Farm is a dairy goat enterprise located in Payakumbuh City that generates substantial quantities of organic waste, including goat manure, feed residues, and liquid effluents from the housing system. However, this waste has not been managed effectively, resulting in environmental pollution risks, reduced barn hygiene and animal welfare, and missed opportunities to create additional economic value for farmers. This community service program aimed to enhance farmers' knowledge and technical capacity through extension and mentoring activities on appropriate technologies for converting livestock waste into organic fertilizers suitable for small-, medium-, and large-scale farming systems. The program was implemented through educational outreach, demonstrations of organic fertilizer production, and hands-on training involving farmers at Toni Farm. The results demonstrated a significant improvement in participants' knowledge and practical skills in producing both solid and liquid organic fertilizers with commercial potential. In addition, the program contributed to reducing environmental problems associated with livestock waste accumulation. The utilization of livestock waste as organic fertilizer is expected to generate additional farm income while promoting the environmental sustainability of dairy goat production. Furthermore, the organic fertilizer produced at Toni Farm has strong potential to be developed into a locally based, environmentally friendly agribusiness product that supports sustainable agricultural development.